Highly virulent form of infectious bursal disease in Egypt: Some epidemiological observations - BEKHIT, A B A (The Indian Journal of Animal Sciences, 2013)
Investigation of 82 severe outbreaks of infectious bursal disease (IBO) in broiler farms, showed differences in mortality rate among the various strains and in the age of susceptibility among the infected flocks. Also the different programmes of vaccination. type of the vaccine, and the time of onset of the disease after vaccination all affected severity of the outbreaks and the mortality rates.Â  Statistically nonsignificant antigenic differences were detected amongst 5 commercial vaccinal strains of standard serotypes 1 and 8 field isolates oflBD virus (IBDV) Hyperimmune rabbit antisera against vaccinal strains and field isolates were used in cross-neutralization tests. Relatedness values were calculated from geometric mean neutralizing antibody titres based on a minimum of 3 tests.